Morphological Parameters of the Hip Joint and Its Relation to Gender, Joint Side and Age—A CT-Based Study - Thelonius Hawellek; Marc-Pascal Meier; Mark-Tilman Seitz; Johannes Uhlig; Ali Seif Amir Hosseini; Frank Timo Beil; Wolfgang Lehmann; Jan Hubert (Diagnostics, 2022)
Background: Physiological reference values for morphological parameters of the hip (MPH) are of clinical importance for the treatment of painful, degenerated or fractured hip joints, as well as to detect morphological deformities, which could result in early osteoarthritis of the hip. Currently, sufficient data for MPH are lacking. Therefore, it remains unclear if age-dependent alterations in adult hip morphology are physiological and if there are side- and gender-dependent differences. The aim of the study was to analyze MPH according to gender, side and age in a large-scaled cohort by CT scans. Methods: A total of 1576 hip joints from 788 patients (female: 257, male: 531; mean age: 58.3 years (±18.9; 18–92 years)) were analyzed by CT. For all hips, acetabular anteversion (AcetAV); lateral centrum edge angle (LCE); acetabular index (AI); femoral neck version (FNV); centrum-collum-diaphyseal angle (CCD); and anterior alpha angle (AαA) were measured. Results: The mean values in this cohort were: AcetAV 20.5° (±6.9); LCE 40.8° (±8.8); AI 0.3° (±5.3); FNV 11.0° (±9.8); CCD 129.9° (±7.4); and AαA 41.2° (±7.7). There was a detectable side-specific difference for AcetAV (p = 0.001); LCE (p < 0.001); CCD (p < 0.001); and AαA (p < 0.001). All the analyzed parameters showed a significant gender-specific difference, except for AI (p = 0.37). There was a significant correlation between age and AcetAV (r = 0.17; p < 0.001); LCE (r = 0.39; p < 0.001); AI (r = −0.25; p < 0.001); CCD (r = −0.15; p < 0.001); and AαA (r = 0.09; p < 0.001), except FNV (p = 0.79). Conclusions: There are side-, gender- and age-specific alterations in hip morphology, which have to be considered in treating hip joint pathologies.